ANALYSIS OF IMPLEMENTATIONS OF THE CRYPTOGRAPHIC HASH FUNCTION SHA-1 BASED ON PIPELINE CIRCUITS - E. V. Listopad (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
An analysis of hardware implementations of the cryptographic hash function SHA-1 based on pipeline circuits with different numbers of logic levels was made in this paper. The hardware implementations of the hash function SHA-1 for high performance applications were described.